PENGARUH PEMBERIAN ZAT PENGATUR TUMBUH TERHADAP PERTUMBUHAN STUM MATA TIDUR KARET (Hevea brasiliensis Muell Arg.) KLON BPM - Yuliantina .; Eddy Usman; Novran Predita (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2013)
This research aimed to assess the effect of alternative plant growth regulators to the growth of stum dorman see rubber Klon BPM 24. This research was done at Lubung Saung Village, District And Banyuasin III Regency South Sumatera Province. This research used a randomized block design with five treatment and five replications. The treatments studied were B0 = 0 ml L-1control, B1 = 2 ml L-1 of water, B3 = 6 ml L-1of water, B4 = 8 ml L-1 of water. Each treatment consisted of 10 plants, with a long soaking the whole treatment is 15 minutes. Thus obtained 25 combined treatment. Each unit experiments are 3 examples of plans. Parameters namely speed sprout observations (HST), shoot length (cm), number of leak stalk (strands), the percentage of seedlings grown (%), weight berangkasan wet plant (g), dry weight of berangkasan plant (g), weight of wet roots departure (g), dan root dry weight berangkasan (g). Based on result obtained it can ce concluded that, the concentration of growth regulators treatment 0f 8 ml L-1 water tends to give the highest yield and better seed to grow that percentage to 80 %, the speed of growth is 20.40 HST shoots, shoot length is 30.79 cm, weight is plants dry berangkasan 7.10 g, wet weight is 1.94 g root, root dry weight is 0.88 g.